2014
DOI: 10.5897/jmpr2013.5328
|View full text |Cite
|
Sign up to set email alerts
|

Genetic homogeneity of vegetatively propagated Clinacanthus nutans (Acanthaceae)

Abstract: Clinacanthus nutans is a medicinal Asian plant often propagated by stem cuttings but little is known about the genetic relationships between existing accessions and the extent of homogeneity. In this study, we examined the genetic homogeneity in 12 C. nutans samples from Malaysia, Thailand and Vietnam reproduced by vegetative propagation from different regions between and within countries, and compared it to sexually propagated Andrographis paniculata (same family), related Clinacanthus siamensis (same family)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Total Phenolic Content of Chocolate The total phenolic content (TPC) of chocolate produced was shown in Table 5. Chocolates with Sabah snake grass leave powder filling (0.16-0.21mg GAE/g chocolate) had significantly higher (p<0.05) TPC content compared to control sample (0.13mg GAE/g dried leaves) because Sabah snake grass leave powder contained high content of phenolic content as reported by Siat (2015). e.…”
Section: Cmentioning
confidence: 56%
See 2 more Smart Citations
“…Total Phenolic Content of Chocolate The total phenolic content (TPC) of chocolate produced was shown in Table 5. Chocolates with Sabah snake grass leave powder filling (0.16-0.21mg GAE/g chocolate) had significantly higher (p<0.05) TPC content compared to control sample (0.13mg GAE/g dried leaves) because Sabah snake grass leave powder contained high content of phenolic content as reported by Siat (2015). e.…”
Section: Cmentioning
confidence: 56%
“…However, the increased in microbial count was lower for chocolate F2. This may due to the fact that Sabah snake grass possess antimicrobial properties (Siat, 2015). Previous research also found that incorporation of herbs into meat products had extended the shelf life of meat products (Lucera et al, 2012).…”
Section: G5mentioning
confidence: 98%
See 1 more Smart Citation
“…The growth habit and leaf appearance of C. nutans are similar to those of Clinacanthus siamensis (Fong et al 2014), but these species have different medicinal properties (Fong et al 2014;Alam et al 2016). Kunsorn et al (2013) conducted macroscopic and microscopic analyses of C. nutans and C. siamensis and found similar morphology and cell components, but the leaf measurement index (palisade ratio, stomata index, and stomatal number) showed different constant numbers.…”
Section: Introductionmentioning
confidence: 95%
“…This plant can be found in most habitats, including dense or open forests, damp fields, bushes, valleys, sea shores, mangrove areas, swamps, and marine regions (Alam et al 2016;Ismail et al 2016). Fong et al (2014) reported that C. nutans grows and primarily reproduces via vegetative propagation, as the flowers are hard to find, which results in severely reduced sexual reproduction. C. nutans is well known for its antioxidant, anti-inflammatory, anticancer, antidiabetic, and antiviral properties (Sakdarat et al 2009;Wanikiat et al 2008;Arullappan et al 2014;Ismail et al 2016).…”
Section: Introductionmentioning
confidence: 99%